Reproductive health services utilization and its associated factors among adolescents in Debre Berhan town, Central Ethiopia: a community-based cross-sectional study - Kenean Getaneh Tlaye; Mesfin Abebe Belete; Tefera Mulugeta Demelew; Mikiyas Amare Getu; Feleke Hailemichael Astawesegn (BMC, 2018)
Abstract Background Utilization of reproductive health services is an important component in preventing adolescents from different sexual and reproductive health problems. As a result, the extent of their service utilization should be determined before implementing any kind of interventions. Therefore, this study was aimed at assessing the level of reproductive health services utilization and its associated factors among adolescents who live in Debre Berhan town. Methods A community-based cross-sectional method was employed in this study from April 5-May 1, 2016. A multi-stage systematic sampling technique was applied to select a total of 648 adolescents living in 5 randomly selected kebeles of Debre Berhan town. Moreover, a logistic regression was done to identify independent predictors of reproductive health service utilization. Results Accordingly, the major findings of this study reveals that about one-third (33.8%) of adolescents utilized at least one of reproductive health services. Adolescents who had discussed sexual and reproductive health issues with their sexual partner and peers were two times more likely to use reproductive health services than their counter parts (AOR = 2.368, 95% CI: 1.168-4.802 and AOR = 2.360, 95% CI: 1.155-4.820 respectively). Adolescents who weren't co-resided with both their parents were also about two times more likely to utilize reproductive health service than those who were living together (AOR = 2.570, 95% CI = 1.155-4.820). Positive perception of oneself towards acquisition of Human Immunodeficiency Virus urged the adolescents to use RH services twice than those who didn't perceive themselves as risky (AOR = 2.231, 95%CI: 1.001-4.975). Conclusion Succinctly speaking, the analysis of the major finding suggests that the utilization of reproductive health services among adolescents in the study area was low. Discussion with sexual partner and peers, risk perception of oneself towards the acquisition of human immune-deficiency virus was among the predictors of reproductive health services usage.